Blockchaining for rewarding consumers for energy saving applications - Jain, Shlok (Nanyang Technological University, 2022)
This project realises the importance of energy conservation and identifies electricity as its means of achieving it. It envisions an energy conservation mechanism via positive incentivisation. The author proposes a reward mechanism powered by blockchain in all households for energy conservation. Each household’s energy consumption is collected and stored in a monthly database. Data is then compared to the specified energy consumption, which has been computed based on the national average given by the Government of Singapore. On such comparison, all households consuming lesser than specified levels will be rewarded via energy coins in their individual household blockchain wallets using a smart contract. The mechanism runs in an automated fashion with no human interference allowing the system to remain free of bias and human error. The aim is to build a culture of energy conservation by making energy coins a lucrative asset, which will incentivise more people to consume energy wisely.